Evaluation of efficacy and safety of glycopyrrolate - xylazine - propofol anesthesia in buffalo calves - Potliya, Sandeep (Vet World, 2015)
AIM: To evaluate the efficacy and safety of glycopyrrolate - xylazine - propofol anesthesia in buffalo calves. MATERIALS AND METHODS: The study was conducted on six clinically healthy male buffalo calves, 6-12 months of age, and weighing between 130 and 170 kg. In all the animals; glycopyrrolate (0.01 mg/kg, IM), xylazine (0.1 mg/kg, IM) and 1% propofol as single bolus (1.5 mg/kg, intravenous), were administered. The parameters observed included behavioral changes, physiological; hematological and blood biochemical parameters. RESULTS: Muzzle and nostrils became dry in all the animals after glycopyrrolate administration. A decrease in spontaneous activity and mild cutaneous analgesia was noticed after xylazine administration. After administration of propofol, loss of swallowing reflex, palpebral reflex, corneal reflexes, periosteal reflex and complete analgesia was observed. There was no significant change in rectal temperature and heart rate. However, heart rate remained elevated during anesthesia. Respiratory rate decreased significantly after propofol administration. There was a significant increase in plasma glucose after the xylazine and propofol administration which remained elevated till recovery. A significant decrease in chloride level was seen after propofol administration. CONCLUSIONS: Glycopyrrolate - xylazine - propofol anesthetic combination may safely be used for short duration anesthesia in buffalo calves.